2013
DOI: 10.1590/s1809-98232013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Fragilidade e funcionalidade entre idosos frequentadores de grupos de convivência em Belo Horizonte, MG

Abstract: ResumoO objetivo do estudo foi verificar a prevalência da síndrome de fragilidade e sua relação com a capacidade e o desempenho funcional em idosos frequentadores de grupos de convivência. O perfil de fragilidade foi determinado por meio dos critérios perda de peso não intencional; exaustão; baixa velocidade de marcha; baixa força de preensão manual e baixo consumo calórico. A capacidade funcional foi avaliada pelo Timed Up and Go (TUG) e o desempenho funcional, pelo índice de Lawton. O perfil de fragilidade f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
2
10
0
8
Order By: Relevance
“…Frail older people showed worse functional performance when compared with the non-frail ones. The authors concluded that these findings reinforce the assumption that frailty compromises the functionality of the elderly (18) .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Frail older people showed worse functional performance when compared with the non-frail ones. The authors concluded that these findings reinforce the assumption that frailty compromises the functionality of the elderly (18) .…”
Section: Discussionsupporting
confidence: 53%
“…We observed that among frail older people, the highest percentage corresponds to partly dependent individuals regarding the IADL. There are studies in the literature that corroborate these findings (13,15,(18)(19) .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The monitoring of health conditions and the functional capacity of this population is crucial to the creation of a care and intervention plan 14 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this, there will be an impact on the social and economic sphere of the country. [1] The increase in life expectancy has two facets, reflecting cultural changes and progress made regarding health and living conditions, such as: reduction of fertility rates, decline in infant mortality, healthier eating habits and greater care with the body. On the other hand, this increase points out to the possibility that the elderly can be affected by degenerative and chronic diseases, without autonomy or dependent on someone´s care.…”
Section: Introductionmentioning
confidence: 99%